Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


4x^2 +4bx-(a+b)(a-b)=4x^2+2x{(a+b)-(a-b)}-(a-b)(a-b)=4x^2+2x(a+b)-2x(a-b)-(a+b)(a-b)=2x{2x+(a+b)}-(a-b){2x+(a+b)}={2x+(a+b)}{2x-(a-b)}= so x=-(a+b)/2 and x=a-b/2
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts